Analysis and Comparison of the Corrosive Behavior of Nickel-Based and Cobalt-Based Dental Alloys - Garcia-Falcon, Carmen Marina; Gil-Lopez, Tomas; Verdu-Vazquez, Amparo; Mirza-Rosca, Julia Claudia (MDPI AG, 2021)
Nickel-based and cobalt-based metal alloys are frequently used in dentistry. The introduction of various elements in the alloy changes its characteristics, and a thorough study of each alloy should be completed to determine its appropriate corrosion resistance and biocompatibility in contact with physiological fluids. There are scarce investigations on these widely used dental alloys in Ringer solution, and findings in this research bring new experimental data and information. The present study evaluated and compared the corrosion behavior of six NiCr- and two CoCr-based dental materials in Ringer solution, using the following techniques: potentiostatic polarization curves (chronoamperometry), microstructural analysis, and EIS (electrochemical impedance spectroscopy). The results obtained in this investigation showed that in the NiCr-based specimens Ni4, Ni5, and Ni6 the stability of the passive layer was destroyed after polarization and a development and growth of stable pits was found in the microstructural analysis after electrochemical treatment. In terms of susceptibility to corrosion, two different groups of specimens were derived from this investigation. A first group which included the two CoCr (Co1 and Co2) and three of the six NiCr alloys studied (Ni1, Ni2, and Ni3). A second group with the other NiCr alloys investigated Ni4, Ni5, and Ni6.
Keywords: metal alloys; NiCr; CoCr; electrochemical characterization; corrosion; Ringer solution